2005
DOI: 10.1093/nar/gki564
|View full text |Cite
|
Sign up to set email alerts
|

The recent transfer of a homing endonuclease gene

Abstract: The myxomycete Didymium iridis (isolate Panama 2) contains a mobile group I intron named Dir.S956-1 after position 956 in the nuclear small subunit (SSU) rRNA gene. The intron is efficiently spread through homing by the intron-encoded homing endonuclease I-DirI. Homing endonuclease genes (HEGs) usually spread with their associated introns as a unit, but infrequently also spread independent of introns (or inteins). Clear examples of HEG mobility are however sparse. Here, we provide evidence for the transfer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…The HEG spreads in the population through the cleavage activity of the HEase, and, once all possible homing sites have been invaded, the HEG is no longer under purifying selection pressure and begins to accumulate mutations and degenerate. For noncoding intron sequences, there may be little pressure for sequence conservation and the sequences that flank the HEG may begin to accumulate mutations (Haugen et al 2005). However, if the HEG happens to evolve such that the HEase targets a new site, such as intron-less versions of the host gene, the HEG then benefits the intron by mobilizing it and allowing it to spread in the genome or to be transferred horizontally along with the HEG (Loizos et al 1994;Zeng et al 2009).…”
Section: Speculations On the Origins Of The Group II Ribozyme/lheg Comentioning
confidence: 99%
“…The HEG spreads in the population through the cleavage activity of the HEase, and, once all possible homing sites have been invaded, the HEG is no longer under purifying selection pressure and begins to accumulate mutations and degenerate. For noncoding intron sequences, there may be little pressure for sequence conservation and the sequences that flank the HEG may begin to accumulate mutations (Haugen et al 2005). However, if the HEG happens to evolve such that the HEase targets a new site, such as intron-less versions of the host gene, the HEG then benefits the intron by mobilizing it and allowing it to spread in the genome or to be transferred horizontally along with the HEG (Loizos et al 1994;Zeng et al 2009).…”
Section: Speculations On the Origins Of The Group II Ribozyme/lheg Comentioning
confidence: 99%
“…8 Finally, the I-PpoI HEG, found within the Ppo.L1925 group I intron in Physarum polycephalum, is transcribed by RNA pol I and translated from an mRNA corresponding to the excised linear group I intron RNA. [9][10][11] Dir.S956-2 is a complex HEG-containing group IC1 intron located within the small subunit (SSU) rDNA of the D. iridis Costa Rica 8 isolate 12 at the exact same location as Dir.S956-1. The HEG is inserted into P8 of the group I intron, but on the opposite www.landesbioscience.com RNA Biologystrand of the one encoding the precursor (pre) rRNA (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Twintrons (30), where two distinct group I introns are associated with each other, and IStrons (77,107), where a group I intron and an insertion sequence (IS) are seen together, are two such cases. Rarely, spliceosomal introns are also found within group I introns (48). As seen below, group I introns also associate with endonucleases.…”
Section: Group I Intronsmentioning
confidence: 94%
“…Several studies have shown that HEs and their corresponding introns or inteins have separate phylogenetic histories (36,46). Also, similar inteins and introns were found to contain different types of HEs, and closely related HEs are known to be encoded within distantly related introns (48). Moreover, "freestanding" endonucleases that are mobile, even without being associated with an intron or an intein, have been found abundantly in some bacteriophage genomes (7,101).…”
Section: Disparate Origins Convergent Parasitic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation